Temporal dynamics of cisplatin-induced endothelial senescence and its association with cognitive impairment: insights into the medial prefrontal cortex - Hei, Yue; Kong, Sheng-nan; Sun, Juan-hua; Liu, Wei-ping; Long, Qian-fa; Zhang, Hong-mei (Frontiers in Oncology, 2025)
BackgroundChemotherapy-related cognitive impairment (CRCI) poses significant challenges for cancer survivors, with its underlying mechanisms remaining inadequately understood, particularly in the medial prefrontal cortex (mPFC). This study aimed to investigate the temporal dynamics of cisplatin-induced endothelial senescence, blood-brain barrier (BBB) integrity, neuroinflammation, and their relationship with persistent working memory impairment.MethodsAdult C57BL/6 mice were treated with cisplatin (2.3 mg/kg) and evaluated at multiple time points post-treatment. Senescence-associated β-galactosidase (SA-β-gal) staining, secretory phenotype (SASP) factors, and expression of p16/p21 proteins were assessed to determine endothelial senescence. BBB integrity was determined using dextran tracer and analysis of tight junction proteins (Claudin-5, ZO-1). Neuroinflammation was investigated via GFAP and Iba1 staining. Cognitive function expression was assessed through the Novel Object Recognition (NOR), Puzzle Box, and modified T-maze tests, focusing on working memory ability.ResultsCisplatin triggered endothelial senescence in the mPFC, peaking at 1 week, as evidenced by elevated percentage of SA-β-gal positive area, increased SASP factors and p16/p21 expression. BBB dysfunction and glial activation emerged later (peaking at 4 weeks), with significant dextran leakage, reduced Claudin-5/ZO-1 levels and increased GFAP and Iba1 staining respectively. Unlike the early vascular events, showing initial rise followed by slow decline, cisplatin-induced working memory impairment persists through 4–12 weeks, manifested as reduced NOR discrimination index, prolonged times in Puzzle Box, and impaired T-maze performance.ConclusionThis study delineates a temporal cascade wherein cisplatin induces early mPFC endothelial senescence with delayed BBB dysfunction and neuroinflammation, driving chronic working memory impairment, thus indicating endothelial senescence as early-stage potential target for mitigating CRCI, especially in mPFC-related working memory deficits.